A Longitudinal Graduate Medical Education Curriculum in Clinical Informatics: Function, Structure, and Evaluation - Rowland, Bradley; You, Jacqueline; Stern, Sarah; Bundy, Richa; Moses, Adam; Witek, Lauren; Obermiller, Corey; Rosenthal, Gary; Dharod, Ajay (Applied Clinical Informatics, 2025)
Background There is a need to integrate informatics education into medical training programs given the rise in demand for health informaticians and the call on the Accreditation Council for Graduate Medical Education and the body of undergraduate medical education for implementation of informatics curricula.Objectives This report outlines a 2-year longitudinal informatics curriculum now currently in its seventh year of implementation. This report is intended to inform U.S. Graduate Medical Education (GME) program leaders of the necessary requirements for implementation of a similar program at their institution.Methods The curriculum aligns with the core content for the subspecialty of clinical informatics (CI) and is led by a multidisciplinary team with both informatics and clinical expertise. This educational pathway has a low direct cost and is a practical example of the academic learning health system (aLHS) in action. The pathway is housed within an internal medicine department at a large tertiary academic medical center.Results The curriculum has yielded 13 graduates from both internal medicine (11, 85%) and pediatrics (2, 15%) whose projects have spanned acute and ambulatory care and multiple specialties. Projects have included clinical decision support tools, of which some will be leveraged as substrate in applications seeking extramural funding. Graduates have gone on to CI board certification and fellowship, as well as several other specialties, creating a distributed network of clinicians with specialized experience in applied CI.Conclusion An informatics curriculum at the GME level may increase matriculation to CI fellowship and more broadly increase development of the CI workforce through building a cadre of physicians with health information technology expertise across specialties without formal CI board certification. We offer an example of a longitudinal pathway, which is rooted in aLHS principles. The pathway requires a dedicated multidisciplinary team and departmental and information technology leadership support.
Keywords: graduate medical education; clinical informatics; longitudinal GME; clinical informatics curriculum